Animal welfare and effects of per-female stress on male and cattle reproduction—A review - Silva, Welligton Conceição da; Silva, Jamile Andréa Rodrigues da; Camargo-Júnior, Raimundo Nonato Colares; Silva, Éder Bruno Rebelo da; Santos, Maria Roseane Pereira dos; Viana, Rinaldo Batista; Silva, André Guimarães Maciel e; Silva, Cleidson Manoel Gomes da; Lourenço-Júnior, José de Brito (Frontiers in Veterinary Science, 2023)
Thermal stress causes severe effects on the wellbeing and reproduction of cattle, including changes in oogenesis and spermatogenesis, generating great concerns, which last for decades. In cattle, the occurrence of thermal stress is associated with a reduction in the production of spermatozoids and ovarian follicles, in addition to the increase of major and minor defects in gametes or in their intermediate stages. In bovine females able to reproduce, a reduction in the rate of estrus manifestation and an increase in embryonic mortality has been observed. Therefore, keeping animals on good welfare conditions, with water supply and in shaded areas can favor the improvement of different reproductive parameters. For all this, the present study aimed to gather, synthesize and argue recent studies related to animal welfare, focusing on the effects of thermal stress on the reproduction of cattle, aiming to support possible strategies to mitigate the harmful effects of thermal stress in this species.